1996
DOI: 10.1016/s1074-7613(00)80302-7
|View full text |Cite
|
Sign up to set email alerts
|

Circulation of Hematopoietic Progenitors in the Mouse Embryo

Abstract: We used a sensitive in vitro culture system to follow, in embryonic blood, the number and state of commitment of B cell precursors along ontogeny. We describe a wave of circulating multipotent progenitors, first detectable at day 10 of gestation, and reaching a maximum in absolute numbers at day 12. They are undetectable by day 14 of gestation, when committed B cell precursors can be detected in fetal liver. Embryonic marrow contains B cell progenitors by day 15. We propose that fetal liver, thymus, and bone m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
110
1

Year Published

1997
1997
2008
2008

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 176 publications
(117 citation statements)
references
References 50 publications
6
110
1
Order By: Relevance
“…By d.p.c. 12 in the mouse, the fetal liver is the site of definitive hematopoiesis, which is marked by the appearance of functional HSCs capable of producing enucleated red blood cells, the full complement of myeloid cells, and at later time points, lymphoid cells [38][39][40]. HSCs from the fetal liver colonize the bone marrow (starting at approximately d.p.c.…”
Section: The Hematopoietic Stem Cellmentioning
confidence: 99%
“…By d.p.c. 12 in the mouse, the fetal liver is the site of definitive hematopoiesis, which is marked by the appearance of functional HSCs capable of producing enucleated red blood cells, the full complement of myeloid cells, and at later time points, lymphoid cells [38][39][40]. HSCs from the fetal liver colonize the bone marrow (starting at approximately d.p.c.…”
Section: The Hematopoietic Stem Cellmentioning
confidence: 99%
“…The haematopoietic site shifts once more in the perinatal period, this time to the BM cavities of the axial skeleton, where adult haematopoiesis will become definitively established. There is evidence suggesting that the BM can be seeded by emergent HSC as part of the same migratory wave that colonises the FL (Delassus and Cumano, 1996;Kumaravelu et al, 2002). The contribution of these early BM HSC to foetal or adult haematopoiesis has not been elucidated.…”
Section: Developmental Contexts In Haematopoiesismentioning
confidence: 99%
“…A second wave of hematopoiesis is initiated in the embryo around E10-E11, when adult-type (definitive) hematopoietic stem cells (HSCs) arise in the aorta gonad mesonephros (AGM) region in close association with the ventral portion of the dorsal aorta and umbilical and vitelline arteries (3). Fate mapping studies in the chick demonstrated that the ECs and HCs that form the ventral floor of the dorsal aorta share a common cellular origin in the splanchnopleural mesoderm (4), and the para-aortic splanchnopleure (P-Sp) of the mouse contains the progenitors of cells that are capable of long-term reconstitution (5). Little is known regarding the in vivo signaling mechanisms that assign both vascular and HSC properties to these anatomically localized mesodermal progenitors.…”
mentioning
confidence: 99%